Ultrasensitive SERS detection of exhaled biomarkers of lung cancer using a multifunctional solid phase extraction membrane - Huang, Yi; Xie, Tianhua; Zou, Kun; Gu, Yingqiu; Yang, Guohai; Zhang, Fanli; Qu, Lu-Lu; Yang, Shikuan (Nanoscale, 2021)
The construction and clinical application of a surface-enhanced Raman scattering (SERS) platform for the early diagnosis of lung cancer could improve the survival rate of patients and would be of great significance. Nevertheless, a sensitive and reusable method for the detection of aldehydes, as biomarkers of lung cancer, in exhaled breath is still an enormous challenge. Aldehydes generally have a low cross section in Raman scattering and have a weak specific affinity to plasmonic nanoparticle surfaces, meaning that sensing them at low concentrations is incredibly difficult. Herein, an ultrasensitive SERS strategy, that can be recycled for further use, for the detection of lung cancer biomarkers in the form of aldehydes was realized by fabrication of a multifunctional Ag NPs@ZIF-67/g-C 3 N 4 solid phase extraction (SPE) membrane. Based on the change in the vibrational fingerprints of 4-ATP before and after reaction with the aldehydes, the SPE membrane was successfully used for the ultrasensitive detection of aldehydes with a detection limit of 1.35 nM. The excellent SERS performance was attributed to the synergistic effect of the densely and closely distributed Ag NPs (providing SERS "hot spots"), ZIF-67 (concentrating the analyte molecules) and g-C 3 N 4 (forming a membrane to prolong the contact time between the aldehydes and the substrate). In addition, recycling of the SPE membrane was achieved by utilizing the self-cleaning ability of the Ag NPs@ZIF-67/g-C 3 N 4 membrane originating from the photocatalytic properties of g-C 3 N 4 . The proposed SERS membrane was easy to operate, rapid and portable, thus providing a potential tool for a point-of-care test in clinical and diagnostic practice. An ultrasensitive and portable SERS platform was developed for detecting aldehydes as lung cancer biomarkers based on a multifunctional SPE membrane.